Teamwork: A Systematic Review of Implications From Psychosocial Constructs for Research and Practice in the Performance of Ultimate Frisbee Games - Amoroso, José Pedro; Rebelo-Gonçalves, Ricardo; Antunes, Raul; Coakley, Jay; Teques, Pedro; Valente-dos-Santos, João; Furtado, Guilherme Eustáquio (Frontiers in Psychology, 2021)
Introduction: Ultimate Frisbee (UF) is a non-contact, challenging, and self-promoted team sport. Some factors such as the game environment and rules seem to influence athletes' behaviour. Goals: Provide a robust systematic review (SR) of the psychological domains associated with UF. Methods: A SR according to Cochrane guidelines was completed. A reproducible search strategy was conducted by two independent reviewers in thirteen online databases: the Cochrane Central Register of Controlled Trials, Web of Science, SCOPUS, B-On, SportDiscus, Scielo; APA PsycINFO, Psychology and Behavioral Sciences; Academic Search Complete; Medline [PubMed]; ERIC; Google Scholar; Open Acess Thesis and Dissertations. The search occurred from 1st to 30th June 2020, and there were no limitations regarding the year of publication. Original papers that contained relevant data regarding psychological domains in the context of UF in English, Portuguese and Spanish were selected. The combination of the main terms "ultimate frisbee" and "sport psychology" was used in all databases. A total of 464 studies were identified and selected in the last phase of selection. After the Screening (n= 301) and Eligibility (n = 71) phases, a total of 30 potential papers were selected and classified. Finally, only four papers were qualified to be included in the final version of SR. Results: The psychological dimensions revealed in the present study were: leadership; basic psychological needs; behaviors; task cohesion and performance; intrateam communication; performance-avoidance goals; friendship goals; sportsmanship associated with goal-directed self-talk and self-regulated learning. Discussion: To our knowledge, this is the first SR about UF. In reviewing all the findings in the studies, there is evidence that UF can promote teamwork, task cohesion, leadership, and increase friendship-approach goals. Conclusion: The results revealed that group goals and promoting teamwork significantly predicted social cohesion and that teamwork and task cohesion was mediated by communication. UF is characterized by communication between all players, whether they are from the same team or the opposing team. In summary, the current study revealed real-time information about the game and its rules. This is important because UF is one of the few team sports worldwide that are self-referred by participants.